2016
DOI: 10.1002/cam4.963
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lapatinib or trastuzumab, alone and in combination, in human epidermal growth factor receptor 2‐positive breast cancer: a meta‐analysis of randomized controlled trials

Abstract: This meta‐analysis compared the efficiency and safety of lapatinib and trastuzumab, alone or in combination, administered with neoadjuvant chemotherapy in patients with human epidermal growth factor receptor 2 (HER2)‐positive breast cancer. For dichotomous variables, the relative risk ratio (RR) and 95% confidence interval (CI) were used to investigate outcome measures: pathological complete response (pCR), neutropenia, diarrhea, dermatologic toxicity, and congestive heart failure (CHF). Eight randomized contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…[40] Similar results are also shown by Xin et al and Xu et al that is, the use of lapatinib and trastuzumab in HER2-positive BC cause skin rash, diarrhoea, neutropenia, and hepatic and other AEs. [49,50] Gianni L, Dafni U, et al found that cardiac toxicity was comparable between anti-HER2 combination therapy and anti-HER2 monotherapy. [51] As we have seen that the previous studies only reported about cardiovascular AEs related to trastuzumab but our study concluded all the systemic AEs along with cardiovascular, more often cardiotoxicity when TKi is given combined with chemotherapy, other systemic toxicities also occur.…”
Section: Discussionmentioning
confidence: 99%
“…[40] Similar results are also shown by Xin et al and Xu et al that is, the use of lapatinib and trastuzumab in HER2-positive BC cause skin rash, diarrhoea, neutropenia, and hepatic and other AEs. [49,50] Gianni L, Dafni U, et al found that cardiac toxicity was comparable between anti-HER2 combination therapy and anti-HER2 monotherapy. [51] As we have seen that the previous studies only reported about cardiovascular AEs related to trastuzumab but our study concluded all the systemic AEs along with cardiovascular, more often cardiotoxicity when TKi is given combined with chemotherapy, other systemic toxicities also occur.…”
Section: Discussionmentioning
confidence: 99%
“…While other meta-analyses have assessed survival and safety between dual- and single-agent HER2-targeted regimens 77 79 , our study compares IMD incidence in these groups and provides the most recent update on the risk of IMD incidence following trastuzumab monotherapy. Our data suggest prolonged survival may not be associated with increased risk of IMD incidence when comparing dual to single HER2-targeted therapy, and when comparing trastuzumab to chemotherapy and observation in early stage disease.…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies or small molecule inhibitors have exhibited clinical efficacy by inhibiting HER2 activity. Besides functioning as an oncogene, HER2 also presents as an excellent tumor antigen, as it is overexpressed in numerous tumors and is rarely expressed in normal tissues (4,8,(43)(44)(45)(46). Vaccines, bispecific antibodies and other approaches have been studied to further improve the clinical outcomes of current HER2 therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Different formats of anti-HER2 bispecific antibodies have been studied previously (15,25,28,45,47,48), including recruitment of T cells in various bispecific antibody formats (17,19,49,50). However, those bispecific antibodies present a number of challenges, including a mixed population during purification, a low yield of production, a tendency to aggregate and a short half-life.…”
Section: Discussionmentioning
confidence: 99%